Implementasi Program Kota Tanpa Kumuh (Kotaku) di Desa Babussalam Kecamatan Rambah Kabupaten Rokan Hulu - Andreal Taqwa; Dadang Mashur (Journal of Research and Development on Public Policy, 2024)
This study aims to find out the implementation of the City Without Slums Program (KOTAKU) in Babussalam Village, Rambah District, Rokan Hulu Regency, as well as what factors hinder its implementation. These policy programs include the development of environmental road infrastructure and environmental drainage. The parties involved are the Rokan Hulu Regency Bappeda, the Rokan Hulu Regency Housing and Residential Areas Office, the Babussalam Village Government, the Babussalam Madani BKM, KSM and the Community. This study aims to analyze the Implementation of the City Without Slums Program (KOTAKU) in Babussalam Village and its Obstacles. The theory used is George C. Edward III (2011) In the book Arifin Tahir (2019), there are 4 indicators of Communication, Resources, Disposition, and Bureaucratic Structure. This study uses a type of qualitative research that is descriptive. With Interview, Observation, and Documentation Data Collection Techniques. The results of the study found that the factors that hinder the implementation of the City Without Slums Program (KOTAKU) in Babussalam Village, Rambah District, Rokan Hulu Regency are: 1.) Difficulties in land acquisition. 2.) The geographical condition of the undulating environment of Babussalam Village. The suggestions from theresearch are expected to be 1. The local government of Rokan Hulu Regency and the Babussalam Village government must further increase efforts in alleviating slum areas, especially in Babussalam Village. 2. It is important for the government to consider revisions or improvements to existing compensation policies, by ensuring that the system provides fair and transparent compensation to affected landowners. 3. Use the scope of in-depth technical studies to understand soil characteristics, select appropriate construction technologies, and involve the active participation of the community in infrastructure maintenance.